The Power of Two: Exploring the Impact of Mothers’ and Fathers’ Involvement in Speech-Language Pathology Treatment for Children with Autism - Noa Kreiser; Osnat Segal (Autism and Developmental Language Impairments)
Purpose This study aimed to investigate the impact of fathers’ and mothers’ involvement in treatments by speech-language pathologists (SLPs) on parent–child communication, play, and feelings of caregiver emotional load in families with children diagnosed with autism spectrum disorder (ASD). Methods Data from 51 families, including 51 fathers and 51 mothers, were analyzed, focusing on measures of involvement in treatments, parent–child play, parent–child communication experience, the child's communication skills, and feelings of caregiver emotional load. Pearson correlations were conducted to explore associations between parental involvement, child variables, and parental factors. Path analysis was employed to delineate the relationships between parental involvement and treatment outcomes. Results Mothers exhibited significantly higher scores in involvement in treatments and feelings of caregiver emotional load compared to fathers, while no significant difference was found in parent–child communication experience. Both fathers and mothers demonstrated direct association between involvement in treatment, enhanced play and better communication experience with their children. Only fathers demonstrated direct associations between involvement in treatment and reduced caregiver emotional load, as well as improved communication skills in their children. The involvement of fathers in treatment mediated the association between paternal education level and the child's gender to treatment outcomes. Communication experience with the child was negatively associated with parental feelings of emotional load. Conclusions Active involvement by both parents is important for supporting parent–child play and communication. Fathers, in particular, experience benefits from involvement in treatments by SLPs, including decreased feelings of emotional load. These findings underscore the significance of considering demographic factors such as parental gender, education level, and the child's gender when designing SLP treatments for children with ASD and guiding their parents